2021
DOI: 10.3390/molecules26144375
|View full text |Cite
|
Sign up to set email alerts
|

Indole- and Pyrazole-Glycyrrhetinic Acid Derivatives as PTP1B Inhibitors: Synthesis, In Vitro and In Silico Studies

Abstract: Regulating insulin and leptin levels using a protein tyrosine phosphatase 1B (PTP1B) inhibitor is an attractive strategy to treat diabetes and obesity. Glycyrrhetinic acid (GA), a triterpenoid, may weakly inhibit this enzyme. Nonetheless, semisynthetic derivatives of GA have not been developed as PTP1B inhibitors to date. Herein we describe the synthesis and evaluation of two series of indole- and N-phenylpyrazole-GA derivatives (4a–f and 5a–f). We measured their inhibitory activity and enzyme kinetics against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…Enzyme kinetics experiments showed that compound 24 (Ki: 3.9 μM) is a noncompetitive inhibitor with stronger binding ability to the enzyme than suramin (Ki: 7.1 μM). 48 Oleanolic acid is a pentacyclic triterpenoid natural product derived from the fruit of Ligustrum lucidum and has pharmacological activities such as inhibition of glucosidase, 49 anti-oxidant, 50 and anti-hyaluronidase. 50 Therefore, researchers modified the C2 and C3 positions of oleanolic acid to obtain compounds with better pharmacological activity.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme kinetics experiments showed that compound 24 (Ki: 3.9 μM) is a noncompetitive inhibitor with stronger binding ability to the enzyme than suramin (Ki: 7.1 μM). 48 Oleanolic acid is a pentacyclic triterpenoid natural product derived from the fruit of Ligustrum lucidum and has pharmacological activities such as inhibition of glucosidase, 49 anti-oxidant, 50 and anti-hyaluronidase. 50 Therefore, researchers modified the C2 and C3 positions of oleanolic acid to obtain compounds with better pharmacological activity.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…Enzyme kinetics experiments showed that compound 24 (Ki: 3.9 μM) is a non-competitive inhibitor with stronger binding ability to the enzyme than suramin (Ki: 7.1 μM). 48…”
Section: Terpene-indole Derivativesmentioning
confidence: 99%
“…Anti-Diabetics-Glucose diffusion inhibitory study: A series of novel pyrazine fused Indole derivatives II-(4a-4l) were evaluated for antidiabetic-glucose diffusion inhibitory activity was decisive by incubating a solution of maltose substrate with Tris volume of buffer pH 8.0 and different concentrations of compounds II-(4a-4l) at 35 0 C. The reaction was commencing by adding 𝛼glucosidase enzyme into the reaction mixture followed by incubation at 35 0 C. Then the reaction was determined by the addition of a colorimetric reagent like DNSA [17]. Ethanol was used as control and it was prepared using the alike procedure replacing the lead molecules.…”
Section: Pharmacological In-vitromentioning
confidence: 99%
“…Interestingly, 18α-GA and 18β-GA were identified as competitive PTP1B inhibitors [ 82 , 83 ]. Two other derivatives of GA, namely, indole- and N-phenylpyrazole-GA, also showed potent non-competitive inhibition of PTP1B [ 84 ].…”
Section: Anti-diabetic Mechanisms Of Gl and Its Derivatives In T2dmmentioning
confidence: 99%